Central Governance Policy and Local Governance Participation: Risk Mitigation of Indonesia Smes Covid-19 Affected - Mahatva Yoga Adi Pradana; Rizaldi Yusfiarto; Ratna Sofiana; Izra Berakon; Muhammad Fiqri Fadillah (Edueksos: Jurnal Pendidikan Sosial & Ekonomi, 2022)
Abstract: The Covid-19 pandemic has a significant impact on the economy, one of the most affected business scales is micro and small businesses. Regarding this potential problem, the central government issued a policy package in the form of financial incentives for various sectors of tourism, aviation and property services, as well as additional subsidies and tax cuts. The author uses a quantitative approach, where data sources are obtained by spreading questionnaires in the Central Java region. Then the results are processed using the SPSS program. Based on this, this study aims to explore how much effectiveness in terms of policy implementation and how the level of local government participation in the policy. The results showed that of the five policies for MSMEs, the provision of working capital incentives has the highest percentage index, this shows that in the short term, the provision of working capital incentives in the form of cash assistance will have a direct impact on MSME.Keywords: Governance Policy, Governance Participation, SMEs Sustainability, Pandemic Covid-19 Abstrak: Pandemi Covid-19 berdampak signifikan terhadap perekonomian, salah satu skala usaha yang paling terdampak adalah usaha mikro dan kecil. Terkait potensi permasalahan tersebut, pemerintah pusat mengeluarkan paket kebijakan berupa insentif keuangan untuk berbagai sektor pariwisata, penerbangan dan jasa properti, serta tambahan subsidi dan pemotongan pajak. Penulis menggunakan pendekatan kuantitatif, dimana diperoleh sumber data dengan menyebarkan kuesioner di wilayah Jawa Tengah. Kemudian hasilnya diolah menggunakan program SPSS. Berdasarkan hal tersebut, penelitian ini bertujuan untuk menggali seberapa besar efektivitas dalam hal implementasi kebijakan dan bagaimana tingkat partisipasi pemerintah daerah dalam kebijakan tersebut. Hasil penelitian menunjukkan bahwa dari kelima kebijakan untuk UMKM tersebut, pemberian insentif modal kerja memiliki indeks persentase tertinggi, hal ini menunjukkan bahwa dalam jangka pendek, pemberian insentif modal kerja berupa bantuan tunai akan berdampak langsung terhadap UMKM.Kata Kunci: Kebijakan Tata Kelola, Partisipasi Tata Kelola, Keberlanjutan UKM, Pandemi Covid-19